Multiple populations of artemisinin-resistant Plasmodium falciparum in Cambodia. - Miotto, O; Almagro-Garcia, J; Manske, M; Macinnis, B; Campino, S; Rockett, K; Amaratunga, C; Lim, P; Suon, S; Sreng, S; Anderson, J; Duong, S; et al. (2013)
We describe an analysis of genome variation in 825 P. falciparum samples from Asia and Africa that identifies an unusual pattern of parasite population structure at the epicenter of artemisinin resistance in western Cambodia. Within this relatively small geographic area, we have discovered several distinct but apparently sympatric parasite subpopulations with extremely high levels of genetic differentiation. Of particular interest are three subpopulations, all associated with clinical resistance to artemisinin, which have skewed allele frequency spectra and high levels of haplotype homozygosity, indicative of founder effects and recent population expansion. We provide a catalog of SNPs that show high levels of differentiation in the artemisinin-resistant subpopulations, including codon variants in transporter proteins and DNA mismatch repair proteins. These data provide a population-level genetic framework for investigating the biological origins of artemisinin resistance and for defining molecular markers to assist in its elimination.